Development of weCope, a mobile app for illness self-management in schizophrenia (Archives of Clinical Psychiatry, 2019)
Objective: To describe the development of weCope, a Portuguese mobile app for people with schizophrenia. Methods: The development of weCope followed 4 stages: I-102 people with psychotic disorders completed an online questionnaire; II-a multidisciplinary focus group was conducted among five mental health professionals; III-we developed the app; IV-9 participants used weCope during 8 weeks to assess its efficiency. Results: weCope targets coping with voices, problem solving, goals setting and stress management, and results indicated that: weCope improved symptoms, sense of recovery and personal and social functioning; 59% of the participants were willing to download an application for illness self-management; professionals revealed some concerns about mHealth but enhanced the high importance to develop these apps; usability testing revealed that 89% considered weCope useful for illness self-management. However, the more years with mental illness, the less importance is given to a mobile application for this purpose. Discussion: weCope was developed through a comprehensive development process and may contribute to a subjective perception of the patient’s better well-being and health condition.